PENGARUH MODEL PEMBELAJARAN SOMATIC AUDITORY VISUALIZATION INTELLECTUAL (SAVI) DENGAN MEDIA FILM TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI IPS MAN MODEL BANDA ACEH - Ayu Safarena; Mawardi .; Anwar Yoesoef (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
The learning process with the Somatic Auditory Visusalization (SAVI) learning model with film media is a learning activity that involves all senses with physical movements, seeing, hearing, and solving problems. The selection of film media can help SAVI learning models be more effective. The study entitled "The Influence of Somatic Auditory Visualization Intellectual (SAVI) Learning Model with Film Media Against Student History Learning Outcomes of Class XI IPS Banda Aceh High School 5" aims to: (1) to analyze the effect of SAVI learning model with film media on the results learn history of class XI students of SMA N 5 Banda Aceh; and (2) to explain what factors influence students' learning history results by using the SAVI model with film media in class XI SMA N 5 Banda Aceh. The approach used in this research is quantitative and qualitative approaches and types of experimental research. The population of this study were all students of class XI SMA N 5 totaling 74 students and consisted of 3 classes, and the sample used was class XI IPS2 consisting of 20 students and XI IPS3 consisting of 20 students. The sample selection used purposive sampling technique. Data collection techniques in this study use tests, documentation, and interviews. The results obtained in this study is the use of the SAVI learning model with film media influences the historical learning outcomes of class XI students of SMA N 5 Banda Aceh. Based on the results of data processing using t-test analysis obtained the value at the level of 5% ( obtained tcount = 3.79 at significant levels ( and opportunities (1-, t(0 , 95) (27) = 2.02 with df = 38-1 = 37. Since 3.79 2.02 then, H0 is rejected and H1 accepted. Factors that can influence student learning outcomes by using the SAVI learning model with film media are that students can understand history learning material better by looking at historical events more clearly in the presence of films. The learning process that utilizes the SAVI learning model with film media can increase students' interest and motivation in studying history, this is due to the utilization of all senses in the learning process and become more effective.Keywords: Somatic Auditory Visualization Intellectual (SAVI) learning model, film media, learning outcomes.